Preparation, characterization, and in vitro activity evaluation of triblock copolymer-based polymersomes for drugs delivery - Besada, Lucas Nahuel (2018)
Polymersomes are polymer-based vesicles that form upon hydration of amphiphilic block copolymers and display high stability and durability, due to their mechanical and physical properties. They have hydrophilic reservoirs as well as thick hydrophobic membranes; allowing to encapsulate both water-soluble bioactive agent and hydrophobic drugs. In this study, poly ethylene glycol (PEG3350 and PEG6000) were used as hydrophilic part and poly(vinyl benzoate) (PVBz) as hydrophobic block to synthesize amphiphilic triblock copolymers (PVBz-b-PEG-b-PVBz). Different proportions of hydrophilic/hydrophobic part were assayed in order to obtain polymersomes by solvent injection method. For the synthesis of the copolymers, the initial block of PEG was derived to obtain a macroinitiator through a xanthate functional group (PEGX3 or PEGX6) and the polymerization of vinyl benzoate was carried out through reversible addition-fragmentation chain transfer polymerization (RAFT). The structure of PEGX and copolymers was confirmed by Infrared, ¹H-NMR and UV-Vis spectrometry, while the average molecular weight (Mw) and polydispersity index (PI) were determined by size exclusion chromatography (SEC). The structures adopted by the copolymers in aqueous solution by self-assembly were investigated using transmission electron microscopy (TEM), dynamic light scattering (DLS) and small-angle X-ray scattering (SAXS). Both techniques confirm that polymersomes were obtained for a fraction of hydrophilic block (f) ≈ 35 ± 10%, with a diameter of 38.3 ± 0.3 nm or 22.5 ± 0.7 nm, as determined by TEM and according to the M; w; of the precursor block copolymer. In addition, we analyzed the possible cytotoxicity in view of its potential application as biomedical nanocarrier. The results suggest that polymersomes seem not induce cytotoxicity during the periods of time tested.